Nutrient gaps and dietary adequacy among adolescent girls in rural north-eastern Ghana: The role of local food-based approaches, school-lunch and multiple-micronutrient fortified biscuits - Azupogo, Fusta; Borgonjen-van den Berg, Karin J.; Aryeetey, Richmond; Brouwer, Inge D. (Cambridge University Press, 2025)
A local food-based approach, including school lunch with multiple-micronutrient fortified biscuits (MMB) as supplementary snacks, may enhance dietary adequacy, although current evidence remains limited. This study assessed nutrient inadequacies and developed food-based dietary recommendations (FBR) incorporating school lunch from the Ghana School Feeding Programme (GSFP) and MMB. Data from 292 girls aged 10–17 years, enrolled in the Ten2Twenty-Ghana study was analysed. Dietary intake was assessed via a quantitative 24-h dietary recall. Usual intakes were estimated using the National Cancer Institute method. Linear programming with Optifood was used to develop FBRs based on commonly consumed foods (≥5% of participants) and their median serving sizes, intake frequency, nutrient content, and cost per 100 g. Constraints included estimated energy needs and harmonised average nutrient requirements. The mean usual energy intake was 2351 (sd 66) kcal/d. Ca (99·8 %), vitamin B12 (99·8 %), riboflavin (96·2 %), vitamin A (91·5 %), vitamin C (87·6 %), Fe (73·7 %), folate (49·3 %) and Zn (8·5 %) inadequacies were prevalent. Optimised diets achieved adequacy for protein and most micronutrients, except Ca and vitamin B12, besides vitamin A for 15–17-year-old girls. School lunch from the GSFP did not enhance micronutrient levels when added to the daily diet. Adding MMB to the daily diet ensured adequacy for vitamin C, riboflavin and Fe, although marginal for Fe. Ca and vitamin A improved substantially with MMB for girls aged 15–17 but remained below the harmonised average requirements. Integrating regular school lunch with specialised fortified foods may be a cost-effective strategy to enhance dietary adequacy for adolescent girls in rural areas.